Water Quality Monitoring A Practical guide to the design and implementation of freshwater quality studies and monitoring programmes - Bartram, Jamie; Ed. Ballance, Richard; Ed (E & FN Spon, 1996)
The approaches and methods for water quality monitoring described in this handbook are based upon the experience gained, over two decades, with the design and establishment of the global freshwater quality monitoring network, GEMS/WATER. The GEMS/WATER programme is co-sponsored by the United Nations Environment Programme (UNEP) and the World Health organization (WHO), together with the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the World Meteorological Organiza tion.